AB0989 Relationship between calcium pyrophosphate dihydrate crystal and osteoarthritis of the knee. (23rd January 2014) - Nishikawa, M.; Owaki, H.; Nakata, K.; Yamada, Y.; Fuji, T.
Abstract : Background: Calcium pyrophosphate dihydrate (CPPD) is one of the common crystals that causes crystal induced arthritis. But the relation between CPPD crystal and osteoarthritis (OA) remains controversy 1 . Is the crystal directly relevant to the development of OA? Is the crystal a byproduct or marker of OA? We don't have enough answer about these questions. Objectives: We investigated the relationship between CPPD crystal and osteoarthritis of the knee. Methods: One hundred forty-four total knee arthroplasties were performed for over grade III OA of knees classified by Kellgren-Lawrence grading scale from September, 2010 to August, 2011. At the operation, joint fluids were collected from 138 knees (average age 74.9: male 19: female 119) and elucidated the CPPD crystal using polarizing microscope. We evaluated the relationship between CPPD crystals, and age, body mass index (BMI), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), matrix metalloproteinase-3 (MMP-3) at the operation. We defined the degree of osteophyte formation as mild, moderate and severe. We also defined the lower extremity alignment as varus (femorotibial angle: FTA =80°), neutral (170° = TA 80°) and valgus (FTA 70°). The relationship between CPPD crystals, and osteophyte formation and lower extremity were also evaluated. Results: CPPD crystals were detected from 43 OA knees (31.2%). There were no significant differences between CPPD(+) and (-) groups about age, BMI, CRP, ESR and MMP-3. Although age, BMI, CRP, ESR and MMP-3 between CPPD(+) and (-) were also evaluated separately in male and female, there were no significant differences. CPPD(+) rate in female (34.5%: 41/119) was significantly higher ( p =0.028) than that in male (10.5%: 2/19). CPPD(+) rate were 63.6% (7/11) in severe osteophyte formed knees, 42.5% (17/40) in moderate osteophyte formed knees and 21.8% (19/87) in mild osteophyte formed knees and there were significant differences ( p =0.003). Although CPPD(+) rate in valgus knees (62.5%, 5/8) was higher than that in varus knees (31.5%, 35/111), there were no significant differences( p =0.083). Conclusions: They are known that the population of Knee OA is mainly female and CPPD arthritis has the possibility to cause incident OA. But there was no report about gender influence about CPPD arthritis 2 . If CPPD crystal is a byproduct or marker of OA, gender does not influence the CPPD(+) rate as previously reported. In this study, we found the CPPD(+) rates in female were significantly higher than that in male. We also found high CPPD(+) rate in severe osteophyte formed knee. These results suggested that CPPD arthritis is the one possible pathogenesis of knee OA and makes it worse through severe osteophyte formation. References: Concoff AL and Kalunian KC. What is the relation between crystals and osteoarthritis? Curr Opin Rheumatol 1999; 11: 436-440. Zhang W, Doherty M, Bardin T, et al. European league against rheumatism recommendations for calcium pyrophosphate deposition. Part 1: terminology and diagnosis. Ann Rheum Dis 2011; 70:563-570. Disclosure of Interest: None Declared